Genetic Variations of Angiotensinogen, Angiotensin Converting Enzyme, and Angiotensin Type 1 Receptor with the Risk of Pulmonary Tuberculosis - Kouhpayeh, Hamidreza; Naderi, Mohammad; Mohammadghasemipour, Zahra; Bahari, Gholamreza; Elahian, Nastaran; Taheri, Mohsen; Hashemi, Mohammad (Prague medical report, 2024)
There is little data regarding the impact of renin-angiotensin system (RAS) gene polymorphisms on tuberculosis. The current study designed to survey the possible association between RAS polymorphisms and the risk of pulmonary tuberculosis (PTB) in a sample of the southeast Iranian population. This case-control study was done on 170 PTB patients and 170 healthy subjects. The AGT rs699 C>T, ACE rs4341 C>G and AT1R rs5186 C>A variants were genotyped using polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) and ACE rs4646994 (287bp I/D) variant by PCR method. Regarding AT1R rs5186 A>C polymorphism, the findings revealed that AC genotype and C allele significantly decreased the risk of PTB (OR=0.39, 95% CI=0.22-0.67, p=0.001, and OR=0.53, 95% CI=0.25-0.72, p=0.002, C vs. A, respectively). The TC genotype and C allele of AGT rs699 T>C significantly associated with decreased the risk of PTB (OR=0.45, 95% CI=0.28-0.74, p=0.002, TC vs. TT and OR=0.51, 95% CI=0.32-0.80, p=0.005, C vs. T, respectively). The ID genotype of ACE 287bp I/D significantly increased the risk of PTB (OR=1.88, 95% CI=1.12-3.17, p=0.017). Our finding did not support an association between ACE rs4341 C>G variant and the risk of PTB. In summary, the findings revealed an association between AT1R rs5186 A>C, AGT rs699 T>C and ACE 287bp I/D polymorphisms and the risk of PTB in a sample of the southeast Iranian population. Further investigation with higher sample sizes and diverse ethnicities are required to confirm our findings.
Keywords: Genotype; Írán; plicní tuberkulóza; angiotensin konvertující enzym; Receptor, Angiotensin, Type 1; Tuberculosis, Pulmonary; angiotensinogen; receptor angiotensinu typ 1; Angiotensin; lidé; genotyp; genetická predispozice k nemoci; studie případů a kontrol; Genetic Predisposition to Disease; Peptidyl-Dipeptidase A; Tuberculosis; Polymorphism; Iran; Case-Control Studies; Angiotensin converting enzyme; polymorfismus genetický; Angiotensin type 1 receptor; Angiotensinogen; Polymorphism, Genetic; Humans